Progress in the study of the mechanism of ferroptosis in coronary heart disease and clinical intervention strategies - Liu, Yingzhi; Yu, Zixuan; Lu, Yuwen; Liu, Yue; Chen, Lingli; Li, Jie (Frontiers in Cardiovascular Medicine, 2025)
Coronary heart disease (CHD), a serious cardiovascular condition with complex and diverse pathogenesis, has recently seen increased attention to the role of ferroptosis—a novel iron-dependent form of programmed cell death. This review synthesizes current research on ferroptosis mechanisms in CHD and emerging clinical intervention strategies. Ferroptosis is characterized by dysregulated iron metabolism, lipid peroxidation, and reactive oxygen species (ROS) accumulation, processes intimately linked to CHD pathophysiology. Under ischemic and hypoxic conditions commonly seen in coronary artery disease (CAD), cardiomyocytes become particularly susceptible to ferroptosis, resulting in cellular dysfunction and diminished cardiac performance. Mechanistic studies have revealed that altered expression of iron metabolism-related proteins (including GPX4, FTH1, TfR1, and HO-1), accumulation of lipid peroxidation products, and disruption of antioxidant defense systems (particularly the Nrf2/GPX4 pathway) are central to ferroptosis progression in cardiac tissue. Clinically, both specific ferroptosis inhibitors (such as Ferrostatin-1) and traditional medicine components (such as Puerarin) have emerged as promising therapeutic candidates, showing cardioprotective effects in experimental models. However, research into ferroptosis mechanisms in CHD remains in its early stages, with significant questions regarding its relationship with other cell death pathways and the clinical efficacy of ferroptosis-targeting interventions requiring further investigation. Future research directions should include in-depth mechanistic exploration and the development of more effective, safer clinical interventions targeting the ferroptosis pathway in cardiovascular disease.